2019
DOI: 10.1002/advs.201900112
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Zinc Phosphate is the Key to Controlling Biocompatibility of Metallic Zinc Implants

Abstract: Recently emerged metallic zinc (Zn) is a new generation of promising candidates for bioresorbable medical implants thanks to its essential physiological relevance, mechanical strength, and more matched degradation pace to that of tissue healing. Zn‐based metals exhibit excellent biocompatibility in various animal models. However, direct culture of cells on Zn metals yields surprisingly low viability, indicating high cytotoxicity of Zn. This contradicting phenomenon should result from the different degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 62 publications
3
59
0
Order By: Relevance
“…On the other hand, biocompatibility is somehow easier to be predicted using in vitro cell-based testing. It is recommended to use a 6–10 times dilution of extracts for in vitro indirect cytotoxicity test for Mg and other biodegradable metals [ [48] , [49] , [50] , [51] ]. There are also some sophisticated setups and methods suggested to be used in vitro to predict the blood compatibility of biodegradable metals [ [52] , [53] , [54] ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, biocompatibility is somehow easier to be predicted using in vitro cell-based testing. It is recommended to use a 6–10 times dilution of extracts for in vitro indirect cytotoxicity test for Mg and other biodegradable metals [ [48] , [49] , [50] , [51] ]. There are also some sophisticated setups and methods suggested to be used in vitro to predict the blood compatibility of biodegradable metals [ [52] , [53] , [54] ].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve the biocompatibility and biofunctions on the implant materials, surface biofunctionalization is one of the easiest ways to change the surface properties which can improve the surface bioactivity, eliminate or control the degradation rate, and prevent implant-related infections, etc. [ [16] , [17] , [18] , [19] ]. For example, surface modification with appropriate coatings can create a favorable surface morphology for the adsorption of proteins in the interactions with biological fluids, and thus promote the cell–extracellular matrix (ECM) interactions and the production of growth factors [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the Sr-loaded phase-transited lysozyme (PTL) coating invokes greater osteogenesis ability by its effects on the immune environment due to the constant release of Sr ions directly at the implant-tissue interface [ 38 ]. Su et al [ 39 ] discovered that the Zn ion that exist in the form of zinc phosphate, plays a key role in improving osseointegration and immune regulation. The immune microenvironment produced by the micro/nanostructured TiO 2 /ZnO coating also showed better capacity to promote osteogenesis macroporous than the TiO 2 coating, which indicated that Zn ion plays an important role in osteoimmunomodulation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%